Development and Validation of Boceprevir using Stability Indicating Reversed-Phase High-Performance Liquid Chromatography Method with Diode Array Detector (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Nowadays, demands for anti-viral drugs have significantly increased in recent years because of globalsusceptibility to viral infections, notably the COVID-19 pandemic and now emergence of human metapneumovirus.Ensuring quality standards and validation of these drugs is essential in healthcare. Boceprevir (BCP) is an antiviraldrug classified as a protease inhibitor, primarily used to treat chronic hepatitis C virus infection, with a particularfocus on genotype 1. Objective: The primary objective is to provide a reversed-phase high-performance liquidchromatography (RP-HPLC) method for the analysis of BCP that is simple, reliable, accurate, and rapid, and tovalidate it as per ICH guidelines with stability-indicating studies. Materials and Methods: The chromatographicanalysis was performed using Ainertsil ODS-3V, C18 (250 mm × 4.6 mm, 5 μm) by GL Sciences. The mobilephase comprised acetonitrile: methanol and buffer (0.05 M potassium dihydrogen phosphate) in a 50:40:10(v/v/v) ratio, with an adjusted pH of 3.5 using orthophosphoric acid. The flow rate was maintained at 0.25 mL/min, with column temperature set at 25°C. Detection was conducted at 206 nm, and the injection volume was20 μL. Results: The BCP exhibited a retention time of 3.69 min. The method demonstrated outstanding linearitywithin the concentration range of 10–50 μg/mL, with a correlation coefficient (r2) value of 0.9998.Validationparameters were evaluated following ICH Q2 guidelines, including limit of detection, limit of quantification,accuracy, precision, robustness, and ruggedness. The % relative standard deviation for all parameters was